2017
DOI: 10.1016/j.palaeo.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Geographic changes in the Aegean Sea since the Last Glacial Maximum: Postulating biogeographic effects of sea-level rise on islands

Abstract: In order to assess how the last sea level rise affected the Aegean archipelago, we quantified the magnitude and rate of geographic change for the Aegean islands during the last sea-level-rise episode (21 kyr BP-present) with a spatially explicit geophysical model. An island-specific Area-Distance-Change (ADC) typology was constructed, with higher ADC values representing a higher degree of change. The highest fragmentation rates of the Aegean archipelago occurred in tandem with the largest rates of sea-level-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 96 publications
0
53
2
Order By: Relevance
“…Smaller islands can be assumed to comprise habitats less uneven in plant species richness, demonstrating higher plant density and, thus, floral resources, and may positively influence species exchange among islands (Sfenthourakis & Panitsa, ). Undoubtedly, species exchange has been much influenced by the Aegean Archipelago's complex geological history (e.g., Messinian Salinity Crisis, Pleistocene changes) (Simaiakis et al., ). Indeed, for the Aegean islands, Pleistocene palaeogeography has been identified as a key factor for the present distribution patterns (Fattorini, ; Poulakakis et al., ) and Pleistocene distances as the drivers of its current biota (Hausdorf & Hennig, ).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller islands can be assumed to comprise habitats less uneven in plant species richness, demonstrating higher plant density and, thus, floral resources, and may positively influence species exchange among islands (Sfenthourakis & Panitsa, ). Undoubtedly, species exchange has been much influenced by the Aegean Archipelago's complex geological history (e.g., Messinian Salinity Crisis, Pleistocene changes) (Simaiakis et al., ). Indeed, for the Aegean islands, Pleistocene palaeogeography has been identified as a key factor for the present distribution patterns (Fattorini, ; Poulakakis et al., ) and Pleistocene distances as the drivers of its current biota (Hausdorf & Hennig, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impact of tectonic events on the palaeogeography of the Aegean realm, global sea-level fluctuations have impacted the extension of emerged areas. Lykousis (2009), Kapsimalis et al (2009) and Simaiakis et al (2017) showed that the Cyclades were separated from mainland Greece during the Middle Pleistocene. The Mega-Cyclades palaeo-island became fragmented into separate islands after the Last Glacial Maximum (LGM) due to the combined sea-level rise and subsidence.…”
Section: Palaeogeographic Context Of Elephants From the Aegean Islandsmentioning
confidence: 98%
“…Indeed, the southern Aegean realm has been subsiding at least since the end of the Miocene (Lykousis 2009, Philippon et al 2014, Simaiakis et al 2017, and references therein). The seismic reflection profiles showed that after the Messinian Salinity Crisis, in the Early Pliocene the sea occupied the Myrtoon Basins and Saronikos Gulf, east of Peloponnese and south of Attiki respectively.…”
Section: Palaeogeographic Context Of Elephants From the Aegean Islandsmentioning
confidence: 99%
See 2 more Smart Citations